Fish and flows: Abiotic drivers influence the recruitment response of a freshwater fish community throughout a regulated lotic system of the Murray‐Darling Basin, Australia. Issue 11 (14th July 2021) - Stocks, Jerom R.; Davis, Sam; Anderson, Marti J.; Asmus, Martin W.; Cheshire, Katherine J.M.; van der Meulen, Dylan E.; Walsh, Chris T.; Gilligan, Dean M.
Abstract: Fish assemblages in dryland rivers have life‐history strategies that have evolved in response to environmental conditions and triggers, particularly water temperatures and flow regimes. The regulation of rivers through the construction of dams, weirs and other water diversion structures has altered natural flow regimes and the associated ecological processes of river systems worldwide. Over a 3‐year period, using standardized fish sampling and daily otolith ageing, the recruitment of eight freshwater fish species was monitored in response to various abiotic drivers, including hydrology and water temperatures, throughout the Macquarie River, a large regulated river system of the Australian Murray‐Darling Basin. A data‐driven statistical classification system is provided that groups species into reproductive guilds, based on their recruitment response to hydrology and water temperature, specifically designed for use in environmental flow management. The eight species were grouped into three distinct reproductive guilds that showed similar recruitment responses to the abiotic drivers. Murray‐Darling rainbowfish, Murray cod, and eel‐tailed catfish were considered as a single guild, characterized by seasonal recruitment during a relatively narrow thermal window under low to moderate stable discharges. The second group included common carp, bony herring, and golden perch, which recruited primarily in association with larger flow events. Un‐specked hardyhead and Australian smelt formed a more differentiated guild, recruiting over a broad range of temperatures and discharges. Limitations associated with using a reproductive guild approach to simplify water management are discussed. This study highlighted important relationships among hydrology, water temperatures, and successful recruitment that can, in turn, be used to inform development of adaptive flow management plans and effective use of environmental water for the conservation management of native fish communities. Important considerations in the design of studies that aim to examine relationships between recruitment and abiotic drivers are also discussed.